COMPARATIVE ANALYSIS OF FOREIGN INVESTMENT ATTRACTION IN ECONOMICS OF THE REPUBLIC OF IRAQ AND THE REPUBLIC OF BELARUS - Haldoon Ibrahim Al-Nuaimi (Наука и техника)
The paper shows what financial incentives, tax and investment laws have been adopted in Iraq and  Belarus for foreign  investment  attraction.  Reasons  for  reduction in direct foreign  investment  flows in these countries have been analyzed in the paper. The paper contains justification of positive features in investment policy of every country that promote an increase of volume and improvement of foreign capital structure in national economics.